Effect of broiler breeder age and glutamine supplementation on the development of the intestinal mucosa of 7-day-old chicks - Maiorka, Alex; Silva, A. V.F.; Santin, E.; Dahlke, F.; Bruno, L. D.G.; Boleli, I. C. [UNESP]; Macari, M. [UNESP]; Trautenmuller, H. (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate the possible effects of glutamine and broiler breeder age on the development of intestinal mucosa in broiler chicks during first week of age. For this purpose, 32 one-day-old broiler chicks were distributed according to a completely randomized experimental design in a 2 × 2 factorial arrangement. Treatments consisted of two broiler breeder ages (30 and 60 weeks) and two dietary glutamine supplementation levels (0% and 1%). The morphological development of intestinal mucosa, particularly villus height and crypt depth, was evaluated. The results showed that the supplementation with 1% of glutamine influenced the development of villus height in the duodenum (p=0.009), jejunum (p = 0.006), and ileum (p = 0.001), as well as crypt depth in the jejunum (p = 0.037) of 7-day-old broilers. These results suggest that the presence of glutamine influenced the development of intestinal mucosa during the first week of age, when these tissues are highly influenced by dietary components, especially by trophic agents. The results show that broiler breeder age (30 or 60 weeks) did not influence the evaluated parameters.
Keywords: Broiler breeder age; Glutamine; Intestinal mucosa; Morphology